Hyperperfusion Counteracted by Transient Rapid Vasoconstriction Followed by Long-Lasting Oligemia Induced by Cortical Spreading Depression in Anesthetized Mice - Unekawa, Miyuki; Tomita, Yutaka; Toriumi, Haruki; Osada, Takashi; Masamoto, Kazuto; Kawaguchi, Hiroshi; Itoh, Yoshiaki; Kanno, Iwao; Suzuki, Norihiro (Journal of cerebral blood flow and metabolism, 2015)
Cortical spreading depression (CSD) involves mass depolarization of neurons and glial cells accompanied with changes in regional cerebral blood flow (rCBF) and energy metabolism. To further understand the mechanisms of CBF response, we examined the temporal diametric changes in pial arteries, pial veins, and cortical capillaries. In urethane-anesthetized mice, the diameters of these vessels were measured while simultaneously recording rCBF with a laser Doppler flowmeter. We observed a considerable increase in rCBF during depolarization in CSD induced by application of KCl, accompanied by a transient dip of rCBF with marked vasoconstriction of pial arteries, which resembled the response to pin-prick-induced CSD. Arterial constriction diminished or disappeared during the second and third passages of CSD, whereas the rCBF increase was maintained without a transient dip. Long-lasting oligemia with a decrease in the reciprocal of mean transit time of injected dye and mild constriction of pial arteries was observed after several passages of the CSD wave. These results indicate that CSD-induced rCBF changes consist of initial hyperemia with a transient dip and followed by a long-lasting oligemia, partially corresponding to the diametric changes of pial arteries, and further suggest that vessels other than pial arteries, such as intracortical vessels, are involved.